THE USE OF LAW IN CHINA IoT OPERATION INTELLIGENCE CONCEPT - Santoso, Syarifurohmat Pratama; Moh. Karim (Sociae Polites, 2023)
Internet of Things (IoT) currently become one of the most developing systems in the world. Private to government used it for their intelligence tools. It will support them to complete mission, such as investigations, security, and recruitment. In international intelligence, IoT concept has already used cause of its effectivity. These conditions are also supported by modern cyber era that can stored our data throughout the world digital form. Currently, China is one of the countries that is making breakthroughs in domestic law to advance its national interests. This research tries to find new points of view and compare data in the form of papers, news, research topic articles, books, and journals. It is hoped that this research can help understand the correlation between law and intelligence regarding the use of IoT in the current era of modern intelligence.